Exploration of dietary diversity and its associated factors among infant and young children in Rural Tamil Nadu - A mixed-method study - Kalaiselvi Selvaraj; Tovia Stephen; S Princy Priyadharshini; Nikita Radhakrishnan; Mohamed Ashic (Wolters Kluwer Medknow Publications, 2021)
Background: A child receiving an acceptable diet is expected to reach the optimal anthropometric measures. More than 60% of dietary requirement has to be met through complimentary diet. Objectives: This aimed to estimate the prevalence of dietary diversity and to assess factors associated with it from caregivers' perceptions by quantitative and qualitative participatory techniques. Methods: A mixed-method study comprising community-based cross-sectional quantitative and participatory rural appraisal qualitative components was conducted in 25 villages from the field practice area of medical institute in South India during 2017. Caregivers of eligible children 6-23 months from villages were interviewed regarding various food groups consumed in the last 24 h using a validated checklist. Association of demographic-, child, and mother-related characteristics with inappropriate dietary diversity was identified using multivariate negative log-binomial model. Results: Of the 603 eligible children, 75.1% had inappropriate dietary diversity. Although inappropriate dietary diversity prevailed across all categories, mothers with less than primary education (adjusted prevalence ratio [PR]: 1.26) children <1 year (adjusted PR: 1.29) and not on current breastfeeding (adjusted PR: 1.15) had significantly more inappropriate diversity. Restraining and motivating forces for dietary diversity were initially recorded from free listing and subjected to force-field analysis. Ignorance, lack of literacy, affordability issues, nuclear family pattern, and influence of junk foods are restraining forces. Conclusion: Inappropriate dietary diversity among 6-23 months children in the rural block of Tamil Nadu, South India, is extensive (75%). Current Child development programs should focus to address these issues based on these identified contextual factors.